HUBUNGAN ANTARA KADAR GULA DARAH SEWAKTU DAN LAMA MENDERITA DENGAN KOMPLIKASI DIABETES MELITUS TIPE 2 DI RUMAH SAKIT PANTI RAPIH - Dita Hanna Febriani (Jurnal Ilmiah Keperawatan IMELDA, 2025)
There are many factors that trigger complications in type 2 diabetes mellitus. Some of them are age, body mass index, hypertension, hyperlipidemia, and smoking. However, there are still inconsistent research results related to random blood sugar levels and duration of suffering with diabetes complications. The aim of this study was to determine the relationship between random blood sugar levels and duration of suffering of diabetes with diabetes complications. This study is a correlational analytical study with a cross-sectional approach involving 150 respondents. Respondents were recruited using a purposive sampling method. Data collection used a demographic data questionnaire and random blood sugar measurements result. The finding of this study indicated that most respondents were women, had low education, and were 59 years old on average. There was no relationship between random blood sugar levels and diabetes complications. There was a significant relationship between duration of suffering with diabetes complications (p = .000). Nurses are expected to be able to provide appropriate interventions as the duration of the patient's illness increases so that patients can manage their condition better.